TRANSACTIONAL AND INTERACTIONAL TALKS IN ESCAPE FROM ALCATRAZ MOVIE - Makdani Kahar, Muh. Nuh Fadly; Arman, Arman; Sofian, Nur Israfyan (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2024)
The objective of this research is to find out what is motive or purpose transactional and interactional talk used in Escape from Alcatraz movie based on McCarthy’s theory. This research used qualitative descriptive method where the source of data was obtained from Escape from Alcatraz movie. The data were collected by watching the movie, coding and classifying the data. The researcher discovered that the movie has a transactional and interactional talk which is Frank Morris during his time in Alcatraz Prison; Morris knew guards treated inmates inhumanely. Seeing this condition, he invited two colleagues to escape from Alcatraz. This plan is almost impossible to carry out, but they are not desperate. They planned in detail what to do to redeem the defensive fortress of Alcatraz. Using transactional talks, slowly but surely, this secret was revealed by Morris by telling the actual situation. Thus, to reveal a secret, sometimes the main character Frank Morris use any transactional talk to disclose deeper information that is deliberately concealed, which happens in this movie. The results showed that Transactional talk is the most dominant compared to interactional talk, because every conversation carried out by the main character Frank Morris is closely related to telling someone something they need to know, exchanging information or giving ideas, and getting someone to do something based on McCarthy’s theory.